'The lesser of two evils…' – views of persons with rheumatoid arthritis on medication adherence: a qualitative study. Issue 6 (2nd June 2016) - Brandstetter, Susanne; Hertig, Simone; Loss, Julika; Ehrenstein, Boris; Apfelbacher, Christian
Abstract : Objective: This study aimed to explore medication adherence among adherent and non-adherent persons suffering from rheumatoid arthritis (RA). A special focus was put on the reasons accounting for successful medication adherence and on potential barriers or facilitating factors. Design: A qualitative study with semi-structured interviews was conducted. Eighteen participants were recruited through stratified purposive sampling according to their medication adherence level. Interviews were analysed by interpretative phenomenological analysis. Results: Medication adherence behaviour was described on a continuum ranging from non-adherent to adherent. Participants' current adherence level was represented as a result of inner negotiations between a variety of influential factors and the successful application of a range of strategies. The influential factors were: experiences with medication, outcome expectations, knowledge of therapeutic options, the traits 'openness' and 'conscientiousness', belief in medical progress, characteristics of the medication, level of trust in one's physician, and perceived autonomy. Facilitating strategies were: establishing routines, using social support and the deliberate suppression of information about potential adverse events. Conclusion: The experience of and the reasons for medication (non-)adherence from the perspective of people with RA were explored comprehensively. Participants' ongoing negotiations between adherence and non-adherence emerged as a key finding with implications for health service providers.